Shane - Schaefer, Jack, 1907-1991 (Houghton Mifflin, 1954)
Wyoming territory, 1889. A mysterious stranger named Shane rides into the Starretts' ranch and learns of the trouble between cattle baron Fletcher and the homesteaders. Shane decides to stay and help the family keep their stake.